Práticas sociais sanitárias, ambiente e saúde no município de Abreu e Lima-PE - Silva, Flávia Maria da (2014)
In Brazil, sanitary conditions experienced by population are admittedly deficient in most of the country. This situation favors the continuity of a reality that involves dissemination of endemic diseases, making the state spends resources on medical care that could be used in disease prevention. In contrast, the society seeks, by its own means, to minimize the social and environmental problems through social practices of strategic use of resources of the territory. However, in some cases, these practices may be ineffective, or even harmful to individual and collective health. Thus, this study aimed to establish a relationship between sanitation, social practices and health, analyzing sanitation infrastructure, with emphasis on sanitary sewage and water supply; sanitary social practices within local social and environmental conditions; and incidence of endemic diseases in the population. For this, as study area four neighborhoods of the municipality of Abreu e Lima (Caetés III, Centro, Fosfato e Planalto), located in the Metropolitan Region of Recife, were used. Besides the intra-urban socio-spatial differences, the study also sought to grasp reality through fieldwork involving questionnaires. Thereby, in possession of these and other data, derived from responsible official bodies, an analysis of the presented situation was carried out, in order to examine how determinants can be these social practices to health of population in face of their environmental conditions. After crossing of this information, poor sanitation infrastructure situation in the municipality could be observed, where the main problems lie in the intermittency of water supply and the absence of a sanitary sewage system in most of municipality. It was also found that, in an attempt to remedy these problems, population acquires specific sanitary practices, such as water storage and construction of rudimentary tanks. Furthermore, even in the neighborhoods where these practices and sanitation infrastructure were considered more appropriate, there was a higher rate of dissemination of waterborne diseases. Therefore, it might be inferred the environment-health-sanitation triad establishes complex relationships that do not obey an immutable logic and, thus, each area gives its particularity, and may have different realities.